"Many wasted months": Stakeholders' perspectives about waiting for speech-language pathology services. (3rd May 2020) - McGill, Nicole; Crowe, Kathryn; Mcleod, Sharynne
Abstract: Purpose: High demand for speech-language pathology services is reflected in long waiting lists. Waiting can be active or passive and has implications for stakeholders, including consumers, professionals, and organisations. The present study explored experiences and perspectives regarding waiting for speech-language pathology services through analysis of stakeholders' written submissions to an Australian Government Senate Inquiry. Method: Written submissions ( n  = 337) were screened for terms related to waiting. Included submissions ( n  = 133) were written by organisations (36.8%), speech-language pathologists (29.3%), parents (27.8%), individuals with communication and/or swallowing difficulties (5.3%), and others. Result: Inductive thematic analysis identified three themes. (1) Duration . Consistently described as long. (2) Consequences . Consumers' consequences included: burden on physical health, finances, time, emotional wellbeing, and relationships, reduced continuity of care, and increased intervention needs. Professional consequences included: stress and burnout impacting job satisfaction, and reduced effectiveness. Societal consequences included: social and ethical burden, and a drain on health and legal systems. (3) Actions . Consumers advocated and sought alternatives (e.g. threats to harm their child, relocation to a capital city), professionals implemented service delivery and policy actions, and organisations lacked effective system-wide strategies. Conclusion: Existing services did not appear to meet stakeholders' needs. Action is needed to improve speech-language pathology waiting lists and access to services, and minimise possible consequences for stakeholders.